A Feasibility study on Handy 4-in-1 Machine - Aquino, Ryan Jose; Deomano, Johanna Jeraldine; Liu, Christopher; Santos, Jose Angel (College of Engineering, 2000)
The target customers of the Handy 4-in-1 Machine were identified as the Local Government Units in Metro MAnila and the surrounding provinces. The market was segmented based on the unit areas identified by the National Statistics Office in the population census. The demand per area was determined by considering the waste generation rates of each area as determined by the MMDA-JICA study on solid waste. IT was found that a large portion of the demand remains unsatisfied by the present supply of shredder machines in the market. surveys conducted by the study team show that the maximum market share attainable by the Machine is 65% of the demand-supply gap. The market share increases linearly for 5 years until the maximum value is reached on the fifth year. The largest demand occurs in the 3rd year where a monthly capacity of 39 machines is needed. Promotions for the Handy 4-in-1 will be composed of product demonstrations and trade show participation. An amount of Php 197,000.00 has been computed as the sales budget. Make or buy analysis has determined that outsourcing the components of the Handy Machine would be a more cost effective than in-house production. A recommended component supplier (RBA Engineering) was identified. Capacity planning has shown that only 2 production workers are needed for the first and fifth years while 4 workers are needed in the second to fourth years. A total floor space of 265 sq m. was determined for the company and a specific site for lease has been identified (Anaconda Building, Pasig) for the company's use. The total project cost based on 3 months working capital has been computed as Php 6,302,589.87. The organizational structure of the company shall follow the corporation form of ownership consisting of the owner and his immediate relatives. This form of ownership was chosen from among other types based on a devised criteria. The company shall be employing a total of nine employees plus tow additional employees on year tow to four. Functions in the company include the manufacturing, the marketing, the sales, the human relations, the purchasing and finance, as well as the logistics. Worker benefits identified include the SSS, the Medicare, and Employee Compensation. The initial investment was determined to be attainable through the equity of the owner and his family members invested as stock in the corporation. The payback period has been determined as 0.09 years or 2 months with a MARR of 40% an IRR of 152.03 and a Net Present Value of Php 16,349,790.54. The Handy 4-in-1 Machine has the following set of benefits for the society. Qualitative benefits include a decrease in garbage generation, improved planting condition, a disease free community, a machine that is proudly Philippine made and gives recognition to the inventor thus inspiring others to do the same. Quantitative benefits include savings on the part of the customer, employment generation and salaries, tax contribution as well as providing business to suppliers. Some social indicators were also computed such as Net Present Value, the Internal Rate of Return and the Benefit-Cost Ratio. The NPV is equal to Php 24,928,900.12, which is greater than 0 and is very favorable. The IRR is equal to 154.73% which is greater than the set 40% discount rate and thus would indicate a socially profitable venture. Finally, the Benefit-Cost Ratio is computed is equal to 1.40, indicating that benefits outweigh costs and therefore resulting into the venture being profitable in all aspects.